Les devoirs de protection et de préservation du milieu marin selon la Convention des Nations Unies sur le droit de la mer à l’aune de la sentence du Tribunal arbitral du 12 juillet 2016 - Jean Ruegg; Maurice Kwan-Chung Yip; Fabien Brial (Études Caribéennes)
The July 12, 2016 award issued by an arbitral tribunal under the United Nations Convention on the Law of the Sea (UNCLOS) has generated a lot of reaction. It settles a dispute between the Philippines and the People's Republic of China (PRC) in the South China Sea (SCS) and sanctions the Chinese authorities on many points. Beyond the geopolitical stakes of this ruling, this article questions one of its facets: the UNCLOS capacity to improve the protection and preservation of marine environments.Based on a corpus drawn from Chinese scientific journals, the authors note that most of the arguments reinforce and legitimize the very firm position of the PRC authorities. The latter have contested the entire arbitration procedure and rejected its conclusions. In their view, the dispute with the Philippines is a matter of sovereignty. It is therefore not within the jurisdiction of UNCLOS. By highlighting the issue of sovereignty, the PRC authorities have avoided commenting on the criticisms contained in the award. They also remained silent about their responsibilities and failures to protect the marine environment. This analysis of the receipt of the July 12, 2016 award illustrates the Convention’s difficulties in achieving its full effects, despite the urgency of the environmental crisis. This conclusion supports the voice of those who call for a profound reform of UNCLOS.